HYPERVENTILATORY CAPACITY - A PREDICTOR OF ALTITUDE SICKNESS - Hayat, Azmat; Hussain, M. Mazhar; Aziz, Sohail; Siddiqui, Abdul Hameed; Hussain, Tassawar (Journal of Ayub Medical College Abbottabad, 2006)
Background: The aim of the study was to document link between hyperventilatory capacity and risk for developing acute mountain sickness (AMS). Methods: This study was carried out at Karakorum Mountain ranges (Northern areas of Pakistan) from March till July 2004. 54 healthy male subjects were enrolled in this study. Arterial oxygen saturation (SpO2) of the subjects was measured by the pulse oximeter at rest and after 1 minute of voluntary hyperventilation at an altitude of 2833 meters. Symptoms of acute mountain sickness (AMS) were recorded on a questionnaire by using the Lake Louise consensus scoring system 24 hours after ascent to high altitude. Results: Mean pre hyperventilation oxygen saturation (SpO2) was 94.07 + 0.26% whereas SpO2 after 01 minute of hyperventilation was 98.61 + 0.14% that was significantly increased (p<0.001). The mean increase in percent oxygen saturation of hemoglobin after one minute of hyperventilation (hyperventilatory capacity) for the study group was 4.61 + 0.24 % while the mean symptom score was 2.06 + 0.26. It was noted that 19 (35.2%) subjects did not develop AMS whereas 34(63.0%) subjects had mild AMS and only one subject developed moderate AMS. There was no case of severe AMS. The data reveals significant (P<0.01) association between hyperventilatory capacity and development of the symptoms of AMS (r= - 0.664). It is evident that individuals with greater hyperventilatory capacity manifest less number of symptoms of mountain sickness. Conclusion: It is concluded that post hyperventilation increase in oxygen saturation at lower altitude may help to predict the susceptibility of subjects to develop high altitude sickness. Keywords: Acute Mountain Sickness, Hyperventilatory Capacity, Hypoxia